The efficacy of Portland cement as a pulpotomy agent in deciduous teeth. Issue 2 (August 2020) - Meslmani, Walid; Kouchaji, Chaza; Rekab, Salem; Abo Fakher, Majid Aljaber; Al Nerabieah, Zuhair
Abstract: Purpose: The objective of this study was to compare the efficacy of Portland cement (Pc) in comparison with Mineral Trioxide Aggregate (MTA) as a pulpotomy agent in primary molars. Materials and methods: 64 Deciduous Mandibular Second Molar of children aged between 6 and 8 years were randomly distributed to either PC or MTA groups which was treated by a conventional pulpotomy technique. The teeth were restored with resin modified glass ionomer cement and stainless-steel crowns. All teeth were assessed clinically and radiographically for success and followed at 3, 6 and 12 months. Results: At 12 months follow-up, the Clinical success rates of MTA and PC were 100% and 93.3% respectively. The radiographic success rate of MTA after 12 months was 96.7% while PC was 93.3% respectively. However, the results showed no significant difference between the two groups. Conclusion: This study finding showed that PC can be used a as pulpotomy agent with high clinical and radiographic success rates similar to MTA. PC may serve as a good alternative to MTA for pulpotomies of primary teeth.